A decreased number of circulating regulatory T cells is associated with adverse pregnancy outcomes in patients with systemic lupus erythematosus. Issue 12 (7th November 2022) - Li, He‐Tong; Zhang, Sheng‐Xiao; Zhang, Jia‐Qi; Cheng, Ting; Liu, Yan; Liu, Hong‐Qi; Hao, Min; Chen, Jun‐Wei
Abstract: Objective: As an autoimmune disease affecting women of reproductive age, systemic lupus erythematosus (SLE) is linked to adverse fetal and maternal outcomes. However, the status of peripheral lymphocytes in SLE patients with different pregnancy outcomes is unclear. This retrospective cross‐sectional study explored the relationship between lymphocyte subpopulations and pregnancy outcomes in married SLE female patients. Methods: The absolute numbers of peripheral T, helper T (Th)1, Th2, Th17, regulatory T (Treg), B, and natural killer (NK) cell subpopulations from 585 female SLE patients and 91 female healthy controls (HCs) were assessed. We compared the lymphocyte subpopulations in SLE patients with HCs and analyzed the absolute number and ratio of Treg cells according to pregnancy outcome in SLE patients. Results: SLE patients had decreased numbers of T, B, NK, Th1, Th2, Th17, and Treg cells and an imbalance in pro‐ and anti‐inflammatory cells ( p  < .05), as well as adverse pregnancy outcomes. In abortion patients, the number of Treg cells ( p  = .008) decreased, leading to an imbalance in effector T and Treg cells. The ratio of Treg cells was higher in SLE patients with nulliparity than in those with one or two parities. Conclusions: The absolute numbers of lymphocyte subpopulations in SLE patients decreased, which was associated with abortion and parity ( p  < .05). These results suggest that a loss of immune tolerance mediated by Tregs triggers pregnancy loss. Abstract : Systemic lupus erythematosus (SLE) is a complex autoimmune disease that predominantly develops among women of childbearing age. Decreased number of regulatory T (Treg) cells and imbalanced Treg ratio was associated with adverse pregnancy outcomes in SLE. Normal Treg cell numbers and function is a prerequisite for healthy ongoing pregnancy.